2020
DOI: 10.1155/2020/5352490
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanisms of the Herbal Components of CRSAS on HK‐2 Cells in a Hypoxia/Reoxygenation Model Based on Network Pharmacology

Abstract: Background. Acute kidney injury is a global problem, which brings a great burden to the society and family. The component of rhubarb, Salvia miltiorrhiza, Astragalus membranaceus, and safflower (CRSAS) has been proved as an useful agent to treat acute kidney injury (AKI) patients in China. Objective. To assess the effect of CRSAS on human renal tubular epithelial cells (HK-2) after the hypoxia/reoxygenation (H/R) and investigate the potential mechanisms. Methods. Network pharmacology was used to predict the po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Network pharmacology shows that the targets of P. igniarius in the treatment of HUA involve the regulation of the apoptotic process, ER stress and the ATF4 transcription factor. Furthermore, studies have shown that ROSinduced chronic ER stress produces a secondary increase in ROS, which usually leads to apoptosis of HK-2 cells [39][40][41]. ER stress is also closely associated with various renal cell injuries and is involved in mediating the development of renal diseases [42][43][44].…”
Section: Discussionmentioning
confidence: 99%
“…Network pharmacology shows that the targets of P. igniarius in the treatment of HUA involve the regulation of the apoptotic process, ER stress and the ATF4 transcription factor. Furthermore, studies have shown that ROSinduced chronic ER stress produces a secondary increase in ROS, which usually leads to apoptosis of HK-2 cells [39][40][41]. ER stress is also closely associated with various renal cell injuries and is involved in mediating the development of renal diseases [42][43][44].…”
Section: Discussionmentioning
confidence: 99%
“…The appropriate IC50 concentration of TGP was determined according to the results of 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay. The hypoxia/reoxygenation (H/R) model in vitro was established by the following steps: 21 HK-2 cells were cultured in the medium free of glucose and serum under the conditions of 1% O 2 , 5% CO 2 and 94% N 2 for 24 h. Thereafter, the cells were cultured in the DMEM containing 10% FBS under the conditions of 21% O 2 , 5% CO 2 and 74% N 2 for 12 h.…”
Section: Methodsmentioning
confidence: 99%
“…e renal tubular epithelial HK-2 cell line was purchased from Shanghai Aiyan Biotechnology Co., Ltd. (Shanghai, China). e HK-2 cells were cultured in Dulbecco's modified Eagle's medium (DMEM) with 10% fetal bovine serum; then, they were placed in incubators at 37°C with 5% CO 2 and passaged 1 time every 3-5 days [15]. After being synchronized with culture for 24 h, the HK-2 cells were placed in 24-well plates at a density of 2 × 10 4 -5 × 10 4 cells per well, and the medium then was covered with tape and sealed for 5 h to simulate the process of ischemia-reperfusion injury.…”
Section: Establishment Model Of H/r and Groupingmentioning
confidence: 99%
“…ere are few reports on the mechanism of SE for the treatment of AKI. To the best of our knowledge, only one study has reported that the SE components of rhubarb, Salvia miltiorrhiza, Astragalus membranaceus, and Safflower (CRSAS) can reduce HK-2 cell apoptosis by inhibiting the expression of CHOP [15].…”
Section: Introductionmentioning
confidence: 99%